2020
DOI: 10.3390/cells9040828
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Homeostasis Modulates Platinum Sensitivity in Human Ovarian Cancer

Abstract: Despite initial chemotherapy response, ovarian cancer is the deadliest gynecologic cancer, due to frequent relapse and onset of drug resistance. To date, there is no affordable diagnostic/prognostic biomarker for early detection of the disease. However, it has been recently shown that high grade serous ovarian cancers show peculiar oxidative metabolism, which is in turn responsible for inflammatory response and drug resistance. The molecular chaperone TRAP1 plays pivotal roles in such metabolic adaptations, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 42 publications
(51 reference statements)
9
44
0
Order By: Relevance
“…However, few reports suggest cancer-promoting or chemoresistant effect on statin treatment [207 , 208] , (209). Low dose treatment of statin promotes its aggressiveness in prostate cancer [208] , likewise treatment of lovastatin in ovarian cancer decreases chemosensitivity towards platinum drugs [209] . Interestingly, in human subjects’ use of statin particularly simvastatin and atorvastatin not only reduce the risk of mortality but also increases survival among pancreatic cancer patients [210] , [211] , [212] .…”
Section: Targeting Cholesterol Metabolism For the Treatment Of Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…However, few reports suggest cancer-promoting or chemoresistant effect on statin treatment [207 , 208] , (209). Low dose treatment of statin promotes its aggressiveness in prostate cancer [208] , likewise treatment of lovastatin in ovarian cancer decreases chemosensitivity towards platinum drugs [209] . Interestingly, in human subjects’ use of statin particularly simvastatin and atorvastatin not only reduce the risk of mortality but also increases survival among pancreatic cancer patients [210] , [211] , [212] .…”
Section: Targeting Cholesterol Metabolism For the Treatment Of Cancermentioning
confidence: 99%
“…In hepatocellular carcinoma cells, it has been shown that 7-Ketocholesterol (7-KC) up-regulates the expression of P-glycoprotein (P-gp) through PI3K/mTOR signaling thereby diminishing the efficacy of doxorubicin [230] . Studies in chemoresistant ovarian cancer cells show more cholesterol uptake via up-regulation of LDLR and a decrease in endogenous cholesterol biosynthesis through downregulation of enzymes involve in cholesterol biosynthesis i.e., Farnesyl Diphosphate Synthase (FDPS) and oxidosqualene cyclase (OSC) [209] .…”
Section: Cholesterol and Resistance To Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol homeostasis plays an important role in the progression of cancer. In ovarian cancer, cholesterol homeostasis may modulate the sensitivity of ovarian cancer patients to platinum-based drugs ( 42 ). Our results suggested that cholesterol-related genes may be involved in drug resistance through cholesterol homeostasis, fatty acid metabolism, and other pathways in gynecological pan-cancer, but these are rarely studied in cervical and endometrial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this cancer is highly chemoresistant and, at present, no second-line therapy with established benefits is available, even though several studies were carried out for this purpose [ 13 , 14 , 15 , 16 , 17 ]. Chemoresistance is the major cause of treatment failure in this setting and is often caused by the activation of several anti-apoptotic pathways [ 18 , 19 , 20 , 21 ], which may act alone or synergistically to sustain cancer cell escape from cytotoxic or cytostatic effects of anticancer agents. Certainly, a better knowledge and/or comprehension of complex mechanisms responsible for drug resistance may improve the management of iCCA patients, suggesting targeted therapy strategies to enhance the response to chemotherapy [ 22 ].…”
Section: Cholangiocarcinoma: From Classification To Treatment Stramentioning
confidence: 99%